Direito animal: histórico e perspectivas - Miranda, Kanthya Pinheiro de (2024)
This work thesis aims to demonstrate a new way of thinking about protection rights dedicated to non-human animals, within the perspective of the national legal system. In an attempt to ward off anthropocentric ideals, that still very influent in Brazilian laws, this paper shows the need to attribute specific fundamental rights to these sentient beings, with therecognition of their value as living creatures that deserve dignity. Throughout the research, is demonstrated the important role of fundamental rights for the protection of basic rights, and the function of the status of dignity, currently attributed only to human beings. Based on an analysis of the most important laws on the subject and on the main theories that justify animalprotection, it is proposed a reflection on how animals are treated by Brazilian legislation and by society, stressing the urgent need for a change of paradigms about these living beings, so that their protection by the legal order can be done in a more relevant and effective way.